Analysis volatile compound of gaharu oil composition via solid phase micro extraction (SPME) - Norsuzieana, Ab Latif (2009)
Gaharu (agarwood) is a fragrant wood that is usually derived from the diseased timber of the genus Aquilaria Thymelaeceae and often occurs as dark coloured patches or streaks in the tree. Due to its strong, unique scent and medicinal properties, gaharu oil is greatly valued as perfumery ingredient and incense. Gaharu may be classified into various grades; Grade A, B, C and D and they are often graded according to the physical properties, gaharu formation and its unique scent. The lower grades such as Grade C are often distilled to obtain gaharu oils. As part of an on-going research on the chemical profiling of some Malaysian gaharu oils and evaluation of their potential beneficial properties; gaharu oils obtained from different sources were analysed and compared by SPME and GCMS. Identification of the chemical components was based on comparison of the types of SPME fibers and chromatographic columns. The SPME device included a fused silica fiber coating partially cross-linked with 100μm Polydimethylsiloxane (PDMS), 75m Carboxen/Polydimethylsiloxane (CAR/PDMS) and 65m Polydimethylsiloxane /divinylbenzene (PDMS/DVB). The chromatographic column used were HP-5MS 5% Phenyl Methyl Siloxane and DB-WAX , 30 m x 250 mm i.d, film thickness 0.25 mm. Examination of the oils showed some variations and differences in terms of GCMS profiles, concentration and chemical components. Majority of the essential oil profiles were complex and made up of sesquiterpenoids and their oxygenated derivatives. However, common occurrences of chemical compounds such as benzaldehyde, 3-phenyl-butanone, alpha-guaiene and gamma- guaiene were detected.